Ischemic Stroke Induced Area Postrema Syndrome With Intractable Nausea, Vomiting, and Hiccups - Cohen, Dylan T (Cureus, 2020)
The area postrema (AP) is a small, circumventricular organ located in the dorsal medulla and is characterized by an anastomosed capillary network with no blood-brain barrier. It contains the chemoreceptor trigger zone for vomiting, which is activated by noxious stimuli in the blood. Lesions to the AP produce a clinical syndrome referred to as area postrema syndrome (APS), which is characterized by intractable nausea, vomiting, and hiccups. APS manifests frequently as neuromyelitis optica spectrum disorders (NMOSD), where antibodies attack aquaporin-4 receptors, which are found in abundance in the AP. Its vascular supply is delivered by the anterior spinal artery or, at times, by small vessel branches of the vertebral artery itself. Ischemic stroke is the fifth leading cause of death in the United States; however, APS due to ischemic stroke has rarely been described. We present a case of a 62-year-old male with ischemic stroke in the cerebellum and brainstem, which produced intractable APS due to extension within his AP. He was treated with metoclopramide 10 mg four times daily and ondansetron 8 mg every eight hours, which relieved his symptoms. Recognizing that the patient’s intractable nausea and vomiting was attributable to AP involvement was valuable in limiting further extraneous workup and focusing on our medical management. Ischemic stroke should be considered in the differential for APS. Given the size of the AP, thin-cut high-resolution diffusion-weighted MRI is warranted in patients with clinical APS. Recognizing that intractable nausea and vomiting may be attributable to stroke is valuable in mitigating extraneous and ineffective medical management. The patient case we describe in our report further outlines these findings.